Urban and Regional Policy and Its Effects - Wolman, Harold; Wial, Howard; Turner, Margery Austin, 1955- (Book collections on Project MUSE., 2014)
The goal of this book, the first in a series, is to bring policymakers, practitioners, and scholars up to speed on the state of knowledge on various aspects of urban and regional policy. What do we know about the effectiveness of select policy approaches, reforms, or experiments on key social and economic problems facing cities, suburbs, and metropolitan areas? What can we say about what works, what doesn't, and why? And what does this knowledge and experience imply for future policy questions? The authors take a fresh look at several different issues (e.g., economic development, education, land use) and conceptualize how each should be thought of. Once the contributors have presented the essence of what is known, as well as the likely implications, they identify the knowledge gaps that need to be filled for the successful formulation and implementation of urban and regional policy.